Improving the Productivity of the Arab Researcher in Light of Globalization Requirements - Bany Eisa, Abdel Raof (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to identify the role of globalization in raising the productivity of the Arab researcher in light of globalization requirements by showing the concept of globalization, its challenges and its implications for the Arab researcher on the social, cultural, economic, political, and media domains. Methods: The researcher followed a descriptive-analytical approach by extrapolating the views of educational scholars and contemporary thinkers to clarify the concept of globalization, its challenges and repercussions, and how the Arab researcher deals with it to improve his/her productivity in light of the requirements of globalization. Results: The results showed how the researcher deals with globalization by increasing cultural awareness and crystallizing a cultural framework and a civilized project at the personal level, so that the individual represents models of goals, ideas, concepts, trends, values and productive behaviors. Conclusions: The study recommends creating more solidarity among researchers through the establishment of scientific societies concerned with research, and the provision of a positive research environment that helps the Arab researcher to advance the level of scientific research, and to develop the methodological tools and techniques that the Arab researcher uses to improve productivity.